Pengaruh PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNA JASA TRANSPORTASI TEMAN BUS PT. TRANS MUSI PALEMBANG JAYA DI KOTA PALEMBANG - Muhammad Deni; Anton Trianto; Arubina Bangsawan; Kemas Welly Angga Permana (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The purpose of this study was to find out: 1. To find out how the quality of service provided by Teman Bus transportation to passengers, 2. To find out how the decision of suit users to the services provided by Teman Bus transportation, 3. To find out how the influence of service quality on the decision of the Teman Bus transportation service user.The sample used in this study were people who had used the Teman Bus transportation service as many as 100 respondents, the data was obtained through 22 questionnaires. The method used in this sampling is by using simple random sampling method. The analytical method used is a quantitative analysis method using path analysis with the SPSS for windows version 24 program. The results of hypothesis testing indicate that there is a significant influence between service quality on service user decisions with a coefficient of determination (R2) obtained of 0.596, which means that there is an influence of the independent variable (service quality) on the dependent variable (service user decisions) of 59.6% and From the t-test, the results show that there is a significant effect of service quality on customer satisfaction on the Teman Bus transportation service with a significance value of t-count (12.013) > t-table (1.9844). Thus the hypothesis explains that Ho is rejected and Ha is accepted.